Thermal enhancement and optical bleaching of thermoluminescence emissions from halite - Ogundare, F.O.; Mashaba, M. (Physica. B, Condensed matter, 2025)
Sodium chloride (NaCl), the mineral known as halite, is a possible phosphor for retrospective dosimetry because of its availability in many locations from its usage in households and for industrial applications. Therefore, the characteristics of thermoluminescence emissions of halite, including thermal enhancement and optical bleaching effects on its thermoluminescence, have been investigated in this study. The glow curve of the halite contains two primary peaks with maximum intensities near 90 and 327°C. The intensities of both peaks are fairly linear with dose below 12 Gy. The peak near 327°C is subject to thermal enhancement with an activation energy of 1.89 eV. The minimum dose that can be measured using the halite was evaluated to be 0.26 mGy. The intensities of both peaks decrease with optical illumination at 470 nm. A band model is proposed to explain TL emission from the halite. Thermoluminescence of the halite is suitable for dosimetry application.